# What is the value of expression cos^2(x-y)+cos^2(x+y)-cos2x*cos2y?

Tushar Chandra | Certified Educator

calendarEducator since 2010

starTop subjects are Math, Science, and Business

We need to simplify the expression (cos (x-y))^2 + (cos (x+y))^2 - cos 2x *cos 2y

(cos (x-y))^2 + (cos (x+y))^2 - cos 2x *cos 2y

=> (cos x * cos y + sin x * sin y)^2 + (cos x * cos y - sin x * sin y)^2 - cos 2x *cos 2y

=> (cos x * cos y)^2 + (sin x * sin y)^2 + 2* (cos x * cos y)*(sin x * sin y) + (cos x * cos y)^2 + (sin x * sin y)^2 - 2* (cos x * cos y)*(sin x * sin y) - cos 2x *cos 2y

=> 2*(cos x * cos y)^2 + 2*(sin x * sin y)^2 - cos 2x *cos 2y

=> 2*(cos x * cos y)^2 + 2*(sin x * sin y)^2 - [(cos x)^2 - (sin x)^2][(cos y)^2 - (sin y)^2]

=> 2*(cos x * cos y)^2 + 2*(sin x * sin y)^2 - (cos x)^2*(cos y)^2 +(cos x)^2 * (sin y)^2 + (sin x)^2 *(cos y)^2 - (sin x)^2 *(sin y)^2

=> (cos x * cos y)^2 + (sin x * sin y)^2  +(cos x)^2 * (sin y)^2 + (sin x)^2 *(cos y)^2

=> (cos x)^2 *[(cos y)^2 + (sin y)^2] + (sin x)^2*[(sin y)^2 + (cos y)^2]

=> (cos x)^2  + (sin x)^2

=> 1

This gives (cos (x-y))^2 + (cos (x+y))^2 - cos 2x *cos 2y = 1

check Approved by eNotes Editorial

giorgiana1976 | Student

We'll use the formula of the cosine of sum or difference of angles and the identity of double angles.

cos(x+y) = cos x*cos y - sin x*sin y

We'll raise to square both sides:

[cos(x+y)]^2 = (cos x*cos y - sin x*sin y)^2

We'll expand the binomial:

[cos(x+y)]^2 = (cos x*cos y)^2 - 2(cos x*cos y*sin x*sin y) + (sin x*sin y)^2 (1)

cos(x-y) = cos x*cos y + sin x*sin y

We'll raise to square both sides:

[cos(x-y)]^2 = (cos x*cos y + sin x*sin y)^2

We'll expand the binomial:

[cos(x-y)]^2 = (cos x*cos y)^2 + 2(cos x*cos y*sin x*sin y) + (sin x*sin y)^2 (2)

We'll add (1) and (2) and we'll get:

[cos(x+y)]^2 + [cos(x-y)]^2 = 2(cos x*cos y)^2 + 2(sin x*sin y)^2 (*)

We'll write the double angle identity:

cos 2x = (cos x)^2 - (sin x)^2 (3)

cos2y = (cos y)^2 - (sin y)^2 (4)

We'll multiply (3) and (4) and we'll get:

cos2x*cos2y = (cos x*cos y)^2 - (cos x)^2*(sin y)^2 - (sin x)^2*(cos y)^2 + (sin x*sin y)^2 (5)

The expresison will become:

E = 2(cos x*cos y)^2 + 2(sin x*sin y)^2 - (cos x*cos y)^2 + (cos x)^2*(sin y)^2 + (sin x)^2*(cos y)^2 - (sin x*sin y)^2

E = (cos x*cos y)^2 + (sin x*sin y)^2 + (cos x)^2*(sin y)^2 + (sin x)^2*(cos y)^2

We'll factorize and we'll get:

E = (cos y)^2*[(cos x)^2 + (sin x)^2] + (sin y)^2*[(sin x)^2 +(cos x)^2]

But, the Pythagorean identity states that:

(cos x)^2 + (sin x)^2 = 1

E = (cos y)^2 + (sin y)^2

E = 1

The value of the expression is E = 1.